2010
DOI: 10.1096/fasebj.24.1_supplement.1024.33
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure independent sexual dimorphism in proteinuric response to high salt intake in Sprague‐Dawley rats.

Abstract: We examined if changes in blood pressure and proteinuria during chronic salt intake exhibit sex disparities in age‐matched male (♂; N=10) and female (♀; N=10) Sprague‐Dawley (SD) rats subjected to either normal (0.7% NaCl) or high salt (8% NaCl) diets for 2‐weeks. Metabolic studies, systolic blood pressures (SBP) measured by tail‐cuff method and proteinuria in 24‐h urine samples, were performed. Baseline SBP was not different between genders (♂:119.1±3 vs. ♀:119.0±4 mmHg) or after 2‐weeks on HS diet (♂:129.0±5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…All this evidence may be also related to the peripheral and renal factors resulting in altered volume handling, thereby leading to high blood pressure. This concept is supported by prior studies, which showed paralleled increased levels in intrarenal renin angiotensin system and profibrotic and proinflammatory factors in response to high blood pressure and diabetic models [ 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 65%
“…All this evidence may be also related to the peripheral and renal factors resulting in altered volume handling, thereby leading to high blood pressure. This concept is supported by prior studies, which showed paralleled increased levels in intrarenal renin angiotensin system and profibrotic and proinflammatory factors in response to high blood pressure and diabetic models [ 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 65%